2011
DOI: 10.1007/s10964-011-9713-z
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Based Victimization Among Adolescents in the School Setting: Emotional Reactions and Coping Behaviors

Abstract: Weight-based victimization is a frequent experience for adolescents, but little is known about their emotional reactions and coping strategies in response to weight-based teasing and bullying. The present study examined the ways that adolescents cope with experiences of weight-based victimization at school. An initial sample of 1,555 students from two high schools in central Connecticut completed a comprehensive battery of self-report measures to assess their experiences of weight-based teasing and bullying at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
244
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 256 publications
(268 citation statements)
references
References 53 publications
16
244
1
7
Order By: Relevance
“…No ambiente escolar, os estudantes com sobrepeso ou obesos encontram maiores obstáculos quando comparados aos colegas eutróficos para a prática de atividade física: podem manifestar uma vergonha evidente, uma preocupação por sua saúde, uma exagerada atenção acerca da perda de peso, ser objeto de vitimização (PUHL;LUEDICKE, 2012;SCARPA et al, 2012), além de relacionar-se negativamente com situações de exercício físico, tendo em vista as experiências precedentes (BALL; CRAWFORD;OWEN, 2000;LYONS, MILLER, 1999). Alguns dados mostram como as crianças com obesidade, comparadas aos colegas eutróficos, reportam mais dias de ausência na escola (GEIER et al, 2007), o que se torna para essas crianças um obstáculo no processo de aprendizagem.…”
Section: Introductionunclassified
“…No ambiente escolar, os estudantes com sobrepeso ou obesos encontram maiores obstáculos quando comparados aos colegas eutróficos para a prática de atividade física: podem manifestar uma vergonha evidente, uma preocupação por sua saúde, uma exagerada atenção acerca da perda de peso, ser objeto de vitimização (PUHL;LUEDICKE, 2012;SCARPA et al, 2012), além de relacionar-se negativamente com situações de exercício físico, tendo em vista as experiências precedentes (BALL; CRAWFORD;OWEN, 2000;LYONS, MILLER, 1999). Alguns dados mostram como as crianças com obesidade, comparadas aos colegas eutróficos, reportam mais dias de ausência na escola (GEIER et al, 2007), o que se torna para essas crianças um obstáculo no processo de aprendizagem.…”
Section: Introductionunclassified
“…Specifically, WBV can increase the risk for behaviors that may contribute to weight gain (eg, increased caloric consumption, binge eating, unhealthy weight control behaviors, increased preference for sedentary activities, skipping physical education [PE] class). [16][17][18] WBV can also have negative psychological outcomes (eg, low self-esteem, depressive symptoms, suicidal thoughts and behaviors) 19 and academic consequences (eg, skipping school, poorer academic performance). 18,20 Weight-based teasing/ bullying may also contribute to social isolation or low peer acceptance of overweight youth.…”
mentioning
confidence: 99%
“…[16][17][18] WBV can also have negative psychological outcomes (eg, low self-esteem, depressive symptoms, suicidal thoughts and behaviors) 19 and academic consequences (eg, skipping school, poorer academic performance). 18,20 Weight-based teasing/ bullying may also contribute to social isolation or low peer acceptance of overweight youth. [21][22][23] Thus, WBV can hinder social, emotional, and academic development of youth, as well as exacerbate adverse health behaviors already associated with obesity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although research has demonstrated that there is a bidirectional relationship between obesity and psychopathology, 19 recently, weight stigma has been reported as an influential factor in the development of psychopathological concerns. For instance, when stigma is internalised, it can lead to stress and lowered self-worth.…”
Section: Stigmamentioning
confidence: 99%